Fracture resistance of rubbers with MWCNT, organoclay, silica and carbon black fillers as assessed by the J-integral: Effects of rubber type and filler concentration - T. Ricco; S. Passera; G. Ramorino; S. Agnelli; J. Karger-Kocsis (eXPRESS Polymer Letters)
The fracture resistance of different rubbers containing various nanofillers, such as multiwall carbon nanotube (MWCNT), organoclay, silica and carbon black (CB), was determined by the J-integral making use of the single edge notched tensile loaded (SEN-T) single specimen approach. The elastomeric matrices were natural (NR), ethylene propylene diene (EPDM) and hydrogenated nitrile rubbers (HNBR). Moreover, the strain softening (Payne effect) of selected rubbers with 30 part per hundred rubber (phr) filler content was also investigated by dynamic mechanical thermal analysis (DMTA) in shear mode. DMTA results indicated that the Payne effect follows the ranking: MWCNT(fibrous) > organoclay(platy) > silica(spherical). J-resistance (JR) curves were constructed by plotting the J value as a function of the crack tip opening displacement (CTOD*), monitored during loading. CTOD* = 0.1 mm was considered as crack initiation threshold and thus assigned to the critical value JIc. JIc increased with increasing filler loading, whereby MWCNT outperformed both silica and CB. On the other hand, JIc did not change with filler loading for the NR/organoclay systems that was traced to straininduced crystallization effect in NR. The tearing modulus (TJ) also increased with increasing filler loading. The related increase strongly depended on both rubber and filler types. Nonetheless, the most prominent improvement in TJ among the fillers studied was noticed for the fibrous MWCNT.